Fibre Bragg grating and no-core fibre in variation of SRI - Rohizad, Siti Nur Aizatti; Daud, Suzairi; Multar, Esmafatinsyafiqa; Tan Halid, Nurul Shuhada; Ahmad Noorden, Ahmad Fakhrurrazi (IOP Publishing, 2020)
In this work, Fibre Bragg Grating (FBG) and no-core fibre (NCF) sensors been investigated in different surrounding refractive index (SRI). FBG with 1550 nm wavelength attached with 5 cm length of NCF is used as SRI sensing probe. The sensitivity of the system was evaluated in different types of solutions which are ethylene glycol (18 % EG, 40 % EG, 60 % EG, 80 % EG, 100 % EG) and glycerol at room temperature. The dependence of the FBG and NCF wavelengths shift in spectral response versus different SRI has shown a linear relationship. The sensitivities of the system were 14.02 nm/RIU and 84.10 pm/RIU for FBG and NCF respectively.